Effect of chemical and heat inactivation on the antigenicity and immunogenicity of Vibrio cholerae. - Cryz, S J (1982)
The effects of heat and chemical inactivation on the antigenicity and immunogenicity of Vibrio cholerae 1418 in rabbits were studied. V. cholerae 1418 was inactivated with heat and chemical inactivants (phenol or Formalin) alone or in combination. Enzyme-linked immunoassay systems employing whole cells of V. cholerae 1418, lipopolysaccharide, or flagella as immobilized antigens were used to measure the antibody response (immunoglobulins G and M) after parenteral immunization of rabbits with various inactivated whole-cell preparations. The "classical" whole-cell vaccine, produced by phenol treatment, was found to be a comparatively poor immunogen. When Formalin was used instead of phenol, the antibody response to all three enzyme-linked immunosorbent assay antigens was greatly increased. Immunoglobulin G titers to intact V. cholerae cells were as much as 100-fold higher in rabbits immunized with the Formalin-inactivated preparation as compared to the classical phenol-inactivated vaccine. Furthermore, antibody produced against the Formalin-inactivated preparation was capable of recognizing antigenic determinants expressed on the cell surface of several heterologous strains of V. cholerae. These results indicate that the antigenicity and immunogenicity of V. cholerae are greatly affected by the inactivation conditions employed for vaccine production and that Formalin is much superior to phenol as an inactivant under the conditions employed in the present study.